Elastic properties of fluid mercury across the metal-nonmetal transition: Ab initio simulation study - Taras Bryk; Oleksandr Bakai; A. P. Seitsonen (Condensed Matter Physics, 2025)
We report an ab initio molecular dynamics study of fluid mercury at temperature 1750 K in the range of densities 7–13.5 g/cm3 . Along this isothermal line we performed an analysis of total charge fluctuations, which make evidence of neutral atom-like screening in fluid Hg for densities less than 9.25 g/cm3 , which practically coincides with the emergence of the gap in electronic density of states. High-frequency shear modulus, high-frequency and adiabatic speeds of sound, shear viscosity, Maxwell relaxation time and dispersion of collective excitations are analyzed as a function of density along the isothermal line.